Stocking density optimisation of pangasius (Pangasianodon hypophthalmus) fingerlings with basil (Ocimum basilicum L.) in nutrient film technique (NFT) based aquaponics: Stocking density optimisation in nutrient film technique (NFT) based aquaponics - Neerudu Harika; Verma, Ajit Kumar; Krishnani, Kishore Kumar; Hittinahalli, Chandrakant Mallikarjun; Varghese, Tincy; Bharti, Vidya Shree; Singh , Angom Lenin; Farooq, Aatira (Indian Journal of Fisheries, 2023)
An experiment for 90 days was performed to optimise the stocking density of pangasius(Pangasianodon hypophthalmus) with basil (Ocimum basilicum L.) in a nutrient film technique(NFT) based aquaponics. The experiment had four treatments with different stockingdensities of pangasius as T1 (2.5 kg m-3), T2 (2.75 kg m-3), T3 (3.0 kg m-3) and T4 (3.25 kg m-3)with a constant plant density of 24 plants m-2 and control viz., C (2.5 kg m-3 withoutplants). Significant (p0.05)difference in macro and micronutrient content of basil leaves was recorded in T4 and T3.The physiological parameters (hematological, serum biochemical and anti-oxidant stressenzymes) were found to be within the acceptable range. Considering the water qualityparameters, fish growth, total biomass of fish, fish physiological responses, basil yield andnutrient content, the stocking density of 3.00 kg m-3 (pangasius) with 24 plants m-2 of basilcould be recommended for basil-pangasius aquaponics.Keywords:Aquaponics, Aquaculture wastewater, Basil,Nutrient film technique, Pangasius